Classes of exact wave functions for general time-dependent Dirac Hamiltonians in 1+1 dimensions - De Castro, A. S. [UNESP] (2003)
The construction of two classes of exact solutions for the most general time-dependent Dirac Hamiltonian in 1+1 dimensions was discussed. The extension of solutions by introduction of a time-dependent mass was elaborated. The possibility of existence of a generalized Lewis-Riesenfeld invariant connected with such solutions was also analyzed.